Rancang Bangun Transformator Untuk Penyearah 24-Pulsa - Junaidi, Junaidi; Anto, Budhi; Suwitno, Suwitno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Multipulse rectifiers are recently used in ac-dc converter to minimize line current distortion due to harmonics. Analysis of the input and output ac-dc converter has been done with the tendency that the number of pulse rectifier most will have a value THD (total harmonic distortion) line current is the smallest and has the greatest power factor. In this study the authors will design and transformers 3-phase make with primary in delta connection and secondary in zigzag connection to produce 12 phases voltage wave, each phase of phase 150. The next phase will output 12 is connected as the input of a 24-pulse rectifier, which consists of 4 units of 3-phase rectifier bridge connection that are arranged in series. Calculation of results rectifier current THD, indicates THD 24-pulse rectifier is lower than the 6-pulse rectifier, THD 24-pulse rectifier currents of 1.41% while the 6-pulse rectifier amounted to 3.61%.Keywords : Multiphase Transformer, Multipulse rectfier, total harmonic distortion of current